2019
DOI: 10.3171/2017.12.jns172480
|View full text |Cite
|
Sign up to set email alerts
|

Microhemorrhagic transformation of ischemic lesions on T2*-weighted magnetic resonance imaging after Pipeline embolization device treatment

Abstract: OBJECTIVE The authors sought to demonstrate that hemorrhagic transformation of ischemic lesions is the main cause of delayed intracerebral hemorrhage (ICH) after Pipeline embolization device (PED) treatment and to estimate the rate of hemorrhagic transformation of new postprocedure ischemic lesions. METHODS Patients who underwent PED placement (PED group) from November 2015 to March 2017 or stent-mediated embolization (EN group) from December 2010 to October 2015 were retrospectively analyzed. Pre- and postpro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…There are several studies regarding d-ICH after endovascular treatment of an UIA, but most were linked to flow diverters (11)(12)(13)(14)(15)(16)(17). Based upon our experience, d-ICH can occur not only in cases with a flow diverter but also in coiling cases, as antiplatelet maintenance is necessary in both situations (especially when a stent is used in coiling cases).…”
Section: Introductionmentioning
confidence: 83%
“…There are several studies regarding d-ICH after endovascular treatment of an UIA, but most were linked to flow diverters (11)(12)(13)(14)(15)(16)(17). Based upon our experience, d-ICH can occur not only in cases with a flow diverter but also in coiling cases, as antiplatelet maintenance is necessary in both situations (especially when a stent is used in coiling cases).…”
Section: Introductionmentioning
confidence: 83%
“…The Neuroform EZ stent was designed for the treatment of intracranial wide-necked and fusiform aneurysms. [ 10 ] The stent not only renders mechanical and hemodynamic benefits for aneurysm occlusion by preventing and repairing coil protrusion into the parent artery but also reduces and modifies the aneurysm inflow pattern adequately. Moreover, it is an excellent option for the intracranial aneurysms located at the bifurcation.…”
Section: Discussionmentioning
confidence: 99%
“…In the systemic review and meta-analysis by Bond et al , the rate of postprocedural DWI documented ischemic lesions was 45%, 44%, 43%, and 67% after simple coiling, balloon assisted coiling, stent assisted coiling, and flow diversion, respectively 23. Single center studies evaluating silent cerebral ischemia after intracranial aneurysm treatment with the PED reported an asymptomatic cerebral ischemia rate of 50.9–90% 4–11. These studies reported an increased risk of post-PED treatment silent cerebral ischemia with female gender,4 aneurysm size ≥10 mm,5 and age ≥60 6…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that management of intracranial aneurysms with the PED-Shield is associated with a lower rate of postprocedural, diffusion weighted imaging (DWI) documented cerebral ischemia than previously reported with the PED 4–11. Hence the purpose of this prospective study was to determine the incidence of cerebral ischemia on postprocedural DWI following PED-Shield treatment of intracranial aneurysms in a single institution cohort of consecutive patients.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation